2005
DOI: 10.1016/j.cell.2005.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Map of Nucleosome Acetylation and Methylation in Yeast

Abstract: Eukaryotic genomes are packaged into nucleosomes whose position and chemical modification state can profoundly influence regulation of gene expression. We profiled nucleosome modifications across the yeast genome using chromatin immunoprecipitation coupled with DNA microarrays to produce high-resolution genome-wide maps of histone acetylation and methylation. These maps take into account changes in nucleosome occupancy at actively transcribed genes and, in doing so, revise previous assessments of the modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

151
1,320
5
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,294 publications
(1,499 citation statements)
references
References 59 publications
151
1,320
5
12
Order By: Relevance
“…We also examined the effects of eliminating Dot1p, an H3K79 histone methyltransferase (38,39). H3K79 methylation is at low levels at yeast telomeres (40), but occurs at high levels at activelytranscribed genes (41). As described below, we found that deletion of SET2 or RPD3 strongly stimulated HIS4 hotspot activity, whereas deletion of HDA1 had a more subtle stimulatory effect.…”
Section: Introductionmentioning
confidence: 80%
“…We also examined the effects of eliminating Dot1p, an H3K79 histone methyltransferase (38,39). H3K79 methylation is at low levels at yeast telomeres (40), but occurs at high levels at activelytranscribed genes (41). As described below, we found that deletion of SET2 or RPD3 strongly stimulated HIS4 hotspot activity, whereas deletion of HDA1 had a more subtle stimulatory effect.…”
Section: Introductionmentioning
confidence: 80%
“…In another study using such arrays, the nuclear pore associated protein Mlp1 was found to associate with alpha-factor-induced genes in an RNA-dependent manner, suggesting a mechanism for chromosome conformational changes in response to the alpha factor mating pheromone [·25]. A separate study used an Agilent DNA microarray containing ∼44,000 60-mer oligonucleotides covering most of the yeast genome at an average probe density of 266 bp to map histone acetylation and methylation at high resolution [26]. In another study, histone methylations in mouse embryonic stem cells were mapped using Affymetrix arrays customdesigned to tile noncoding regions that are highly conserved over mammalian genomes and may be important for gene regulation during development [27].…”
Section: Chip-chipmentioning
confidence: 99%
“…There have been recently many studies of mapping histone occupancies together with their modifications in DNA sequences and of relationship between them and various genetic activities concerning DNAs [1,2,5,7,16,18,19]. But most of these studies were experimentally conducted by the combination of chromatin immunoprecipitation and whole-genome DNA microarrays, or ChIP-Chip protocol.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of acetylation and methylation occurs at specific highly conserved residues in the histone components of nucleosomes: acetylation sites include at least nine lysines in histone H3 and H4 (H3K9, H3K14, H3K18, H3K23, H3K27, H4K5, H4K8, H4K12, and H4K16); methylation sites include H3K4, H3K9, H3K27, H3K36, H3K79, H3R17, H4K20, H4K59, H4R3 [14]. When a nucleosome appears in a specific DNA sequence area, these potentially sites can have a certain acetylation or methylation level [5,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation